2016
DOI: 10.1111/hel.12363
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and its related factors in junior high school students in Nagano Prefecture, Japan

Abstract: The prevalence of H. pylori infection is as low as 3% among junior high school students aged 12-15 years in Japan. The disappearance of H. pylori is accelerating in Japanese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 46 publications
3
29
2
Order By: Relevance
“…The study population consisted of thirteen subjects with serum/urinary H pylori antibody positivity, who agreed to enrollment in the H pylori epidemiological study performed as a part of a lifestyle‐related disorder prevention program at four junior high schools in Nagano and received eradication therapy at our university hospital in Nagano between 2012 and 2015. The detail regarding the epidemiological study and part of results were previously published . In this study, we updated the epidemiological data with addition of data collected for 2014‐2015.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population consisted of thirteen subjects with serum/urinary H pylori antibody positivity, who agreed to enrollment in the H pylori epidemiological study performed as a part of a lifestyle‐related disorder prevention program at four junior high schools in Nagano and received eradication therapy at our university hospital in Nagano between 2012 and 2015. The detail regarding the epidemiological study and part of results were previously published . In this study, we updated the epidemiological data with addition of data collected for 2014‐2015.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we conducted an epidemiological study screening for H pylori antibody positivity to clarify the prevalence of H pylori infection among Japanese junior high school students. The results indicated a prevalence of 3.1% among junior high school students in Nagano Prefecture, Japan . However, the clinical features of infected children and adolescents, such as the extent of gastritis or gastric atrophy and associations with abdominal pain and anemia, have not been clearly defined.…”
Section: Introductionmentioning
confidence: 96%
“…Studies from Japan have also shown a considerable fall of H. pylori prevalence in childhood. One study from a high GC incidence area found only 85 of 1,765 (4.8%) students aged 13‐15 years to be positive, and in another the prevalence in school children aged 12‐15 years was 3.1% . Inoue reported that Japanese generations born before 1950 have a high prevalence of around 80%‐90%, decreasing with age to reach around 10% or less in those born around the 1990s, and less than 2% for those born after year 2000.…”
Section: Prevalence Of H Pylori and Recent Changesmentioning
confidence: 99%
“…H. pylori status was assessed by ELISA and then by UBT. The overall prevalence of H. pylori was 3.1% (14/454) …”
Section: Epidemiologymentioning
confidence: 99%